2003
DOI: 10.1046/j.1365-2648.2003.02501.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient injury and physical restraint devices: a systematic review

Abstract: Many of the findings highlight the urgent need for further investigation into the use of physical restraint in health care facilities. Further research should investigate the magnitude of the problem and specific restraint devices associated with injury. However, given the limited nature of the evidence, this association should be investigated further using rigorous research methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
240
1
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(258 citation statements)
references
References 32 publications
5
240
1
12
Order By: Relevance
“…The use of restraints may exacerbate BPSD and can also lead to numerous physical problems. For example, reducing mobility through the use of bed rails can lead to an increase risk of deep vein thrombosis, pressure sores, constipation, delirium, or chest infections (Evans et al ., 2003; Inouye and Charpentier, 1996). Of the study population, 201 (87.4%) lacked the capacity to provide consent to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The use of restraints may exacerbate BPSD and can also lead to numerous physical problems. For example, reducing mobility through the use of bed rails can lead to an increase risk of deep vein thrombosis, pressure sores, constipation, delirium, or chest infections (Evans et al ., 2003; Inouye and Charpentier, 1996). Of the study population, 201 (87.4%) lacked the capacity to provide consent to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to implement the Society of Critical Care Medicine guidelines to limit the use of physical restraint, more efforts should be made to alert nursing staff on the harmful effects of using physical restraint and to suggest alternatives. 3,11 One of the strengths of our study is that the study population is a good representation of the Dutch ICU population. A large number of patients were included from 25 ICUs, creating a study sample of a quarter of all Dutch ICUs.…”
Section: Multivariate Univariatementioning
confidence: 99%
“…2 The effectiveness of physical restraint has never been studied in a randomized clinical trial, and evidence of harmful effects associated with physical restraint is increasing. In addition to local injury of the skin and peripheral nerves, 3 the use of physical restraint has been associated with risk for delirium 4,5 and posttraumatic stress disorder. [2][3][4][5][6] Furthermore, the use of physical restraint may be regarded as humiliating by awake patients and their relatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evans et al conducted a systematic review of patient injury and physical restraint devices [6]. The researchers found that physical restraint may increase the risk of death, falls, serious injury and increased duration of hospitalization.…”
Section: Adverse Effects Of Restraint Usementioning
confidence: 99%